Korelasi Profil Kepribadian Minnesota Multiphasic Personality Inventory-2 (MMPI-2) dengan Indeks Prestasi Semester Pertama Mahasiswa Baru Fakultas Kedokteran Universitas Pattimura Tahun Akademik 2025/2026 - Adnan Triputra Surya; Johan Bension; Genevieva E. Tanihatu (Universitas Muhammadiyah Manado, 2026)
First-year medical students are particularly vulnerable to psychological problems due to the challenges of adapting to a new academic environment and increased academic demands, which may adversely affect their academic performance. The Minnesota Multiphasic Personality Inventory-2 (MMPI-2) is a widely used instrument for assessing psychological functioning and personality characteristics. This study aimed to examine the correlation between MMPI-2 results and first-semester Grade Point Average (GPA) among first-year medical students enrolled in the 2025/2026 academic year at the Faculty of Medicine, Universitas Pattimura. This analytical observational study employed a cross-sectional design with a total sampling technique. Secondary data, including MMPI-2 results and first-semester GPA, were obtained from 146 eligible students. Spearman's rank correlation test was used to analyze the association between MMPI-2 scales and academic performance. Most students demonstrated MMPI-2 profiles within the normal range across both clinical and supplementary scales. However, the highest proportions of clinically elevated scores were observed on the Schizophrenia (Sc), Psychasthenia (Pt), and Depression (D) clinical scales, while the supplementary scales with the highest elevated scores were Addiction Admission (AAS), Hostility (Ho), and Anxiety (A). Correlation analysis showed that only Hypochondriasis (Hs) and Depression (D) were significantly and negatively associated with first-semester GPA among the clinical scales. Among the supplementary scales, Anxiety (A) and College Maladjustment (Mt) showed significant negative correlations with GPA, whereas Ego Strength (Es), Dominance (Do), and Addiction Potential (APS) showed significant positive correlations.